2019
DOI: 10.20944/preprints201903.0048.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Application of Adaptive Kalman Filter in Online Monitoring of Mine Wind Speed

Abstract: The underground complicated testing environment and the fan operation instability cause large random errors and outliers of the wind speed signals. The outliers and large random errors result in distortion of mine wind speed monitoring, which possesses safety hazards in mine ventilation system. Application of Kalman filter in velocity monitoring can improve the accuracy of velocity measurement and eliminate the outliers. Adaptive Kalman Filter was built by automatically adjusting process noise covariance and m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Fig. 4 shows the original wind speed profile after Kalman filtering (KF) ( [8]) from 12:00 to 12:10. By filtering the noise signal, the overall wind speed dynamic trend is obtained from the complex raw field data.…”
Section: Denoising Of Wind Speedmentioning
confidence: 99%
“…Fig. 4 shows the original wind speed profile after Kalman filtering (KF) ( [8]) from 12:00 to 12:10. By filtering the noise signal, the overall wind speed dynamic trend is obtained from the complex raw field data.…”
Section: Denoising Of Wind Speedmentioning
confidence: 99%
“…To correct monitoring data errors, experiments have shown that the turbulence data represented by mine ventilation data were consistent with Gaussian noise [13]. A computation-feedback-correction mechanism for the accurate correction of wind resistance data obtained during ventilation has been proposed to calculate roadway airflow [14]. An adaptive Kalman filter based on an expectation-maximization algorithm was proposed to shield fluid pulsations while preserving system-induced fluctuations [15].…”
Section: Introductionmentioning
confidence: 99%
“…however, there are few studies on cleaning methods of mine speed monitoring data in coal mines. huang et al [18] used the Laser Doppler Velocimetry system to obtain wind speed data and applied the adaptive Kalman filter model to clean outliers of wind speed data. however, when the data is missing for a long time, the data after cleaning by this method has a large deviation from the original.…”
Section: Introductionmentioning
confidence: 99%